2022
DOI: 10.1002/app.52974
|View full text |Cite
|
Sign up to set email alerts
|

From waste to wealth: A critical review on advanced materials for EMI shielding

Abstract: Solid waste generation has increased enormously due to development in a fast‐moving world. Large amounts of industrial and agricultural waste are either incinerated or subject to landfilling, accounting for increasing air and water pollution. The 3 “R”s of waste management, reduce, reuse, and recycle, in most cases, deduce themselves to a theoretical topic. However, a stage has reached where the primary importance should be given to waste management and sustainable development where reprocessing the materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…On the other hand, higher content of ferrites is also connected with formation of magnetic dipoles on ferrites particles, which is then beneficial for higher complex permeability of composites filled with CB and 300 phr of ferrites. Although, in general, materials with high permeability have been reported to be better materials for absorption shielding, 45,46 in this case, higher conductivity and permittivity of the composites with higher ferrites loading are the main factors, while those composites exhibited poorer EMI absorption shielding performance. It has been shown that the higher was the conductivity of composites, the lower was their absorption shielding performance.…”
Section: Resultsmentioning
confidence: 84%
“…On the other hand, higher content of ferrites is also connected with formation of magnetic dipoles on ferrites particles, which is then beneficial for higher complex permeability of composites filled with CB and 300 phr of ferrites. Although, in general, materials with high permeability have been reported to be better materials for absorption shielding, 45,46 in this case, higher conductivity and permittivity of the composites with higher ferrites loading are the main factors, while those composites exhibited poorer EMI absorption shielding performance. It has been shown that the higher was the conductivity of composites, the lower was their absorption shielding performance.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, electromagnetic radiation interferes with the normal operation of equipment, causing electronic equipment failure, which leads to serious losses in military and civil applications. Besides, electromagnetic waves can affect the human body, causing different degrees of damage to various organs and tissues [ 86 ]. Recent studies have pointed out that these forms of radiation can lead to depression, suicidal tendencies, children’s ADHD, and neuropsychiatric disorders, as well as abnormal births [ 86 ].…”
Section: Electromagnetic and Radiation Pollutionmentioning
confidence: 99%
“…Besides, electromagnetic waves can affect the human body, causing different degrees of damage to various organs and tissues [ 86 ]. Recent studies have pointed out that these forms of radiation can lead to depression, suicidal tendencies, children’s ADHD, and neuropsychiatric disorders, as well as abnormal births [ 86 ]. More importantly, with the development of 5G technology in recent years, people who are often accompanied by mobile phones and computers have become increasingly worried about the health implications of electromagnetic radiation.…”
Section: Electromagnetic and Radiation Pollutionmentioning
confidence: 99%
“…A large quantity of industry waste is either burned or subject to land filling, resulting in the growth of pollutions. 1 Nowadays, with the improvement of living standards, people's demand for plastics continues to increase, and the cumulative amount of plastics in the environment also increases. 2 Plastic will be broken into smaller plastic fragments by photodegradation and biodegradation in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Solid waste generation has amplified extremely due to its growth in a speeding world. A large quantity of industry waste is either burned or subject to land filling, resulting in the growth of pollutions . Nowadays, with the improvement of living standards, people’s demand for plastics continues to increase, and the cumulative amount of plastics in the environment also increases .…”
Section: Introductionmentioning
confidence: 99%